2005
DOI: 10.1615/jenvpathtoxoncol.v24.i2.50
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Apoptosis with Comet Formation Induced by Tea Polyphenols in Human Leukemia Cells

Abstract: Induction of apoptosis is an important approach to cancer control. Apart from morphological changes in cells, apoptosis is characterized by fragmentation of nuclear DNA. The characteristic DNA ladder formation that is observed on gel electrophoresis does not reflect the DNA breakdown in individual cells; contributions from small subpopulations are usually overlooked. On the other hand, alkaline comet assay as measured by single cell gel electrophoresis accurately measures DNA fragmentation at a single cell lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The SGCE technique has been used in numerous in vitro investigations to study antioxidant effects of individual compounds and complex mixtures in stable cell lines and in human lymphocytes. Typical examples are investigations of flavonoids by Anderson and coworkers with blood and sperm cells ( 280 , 281 ) , experiments concerning antioxidant effects of coffee and its constituents ( 282 ) , studies on the protective effects of tea catechins ( 283 , 284 ) to name only a few. Also quite a substantial number of in vivo studies with laboratory animals have been published, e.g.…”
Section: Conventional and New Methods For The Detection Of Dietary Anmentioning
confidence: 99%
“…The SGCE technique has been used in numerous in vitro investigations to study antioxidant effects of individual compounds and complex mixtures in stable cell lines and in human lymphocytes. Typical examples are investigations of flavonoids by Anderson and coworkers with blood and sperm cells ( 280 , 281 ) , experiments concerning antioxidant effects of coffee and its constituents ( 282 ) , studies on the protective effects of tea catechins ( 283 , 284 ) to name only a few. Also quite a substantial number of in vivo studies with laboratory animals have been published, e.g.…”
Section: Conventional and New Methods For The Detection Of Dietary Anmentioning
confidence: 99%
“…The intrinsic, via caspase 9, and extrinsic, via caspase 8, apoptotic pathways converge on the downstream effector caspase 3 (Rathmell and Thompson, 1999). Capase 3 was found to play an important role in DNA damage via MN and comet assays (Decordier et al, 2008, Kundu et al, 2005. In this study, BAPP was found to upregulate the activation of caspases 3, 8, and 9, and this demonstrated the signal transduction pathway of BAPP-induced apoptosis in HGFs.…”
Section: Discussionmentioning
confidence: 50%
“…An explanation of the ability of oxidative stress to cause DNA damage is that it triggers a series of metabolic events within the cell that lead to the activation of nucleases, which cleave the DNA backbone. Recently, there have been many debates concerning the hypothesis that oxidative stress can cause rises in intracellular free calcium that might break DNA by activating calcium-dependent endonucleases in a mechanism similar to apoptosis ( ).…”
Section: Discussionmentioning
confidence: 99%